Gestão estratégica nas polícias militares: um estudo sobre a polícia militar de Minas Gerais e a brigada militar - Silva, Cilon Freitas da (2017)
Considering that public safety is the duty of the State and the responsibility of all, according to the provisions of Article 144 of the Federal Constitution, to assure it in the current context of extreme violence and crime, is the daily challenge of all public and social sectors, in particular, of the police in Brazil. However, old traditional formulas and management tools based on patrimonialist or bureaucratic management models, which are still common in the administration of public security organizations in Brazil, need to be revised in order to provide better services and achieve effective results in the area. In order to contribute to this process, this study analyzes the management of the military police of Minas Gerais (PMMG) and Rio Grande do Sul (BMRS), from 2003 to 2014. The final objective is to highlight the main factors of influence, strategies based on management theory and identify good managerial practices that can be replicated. To do so, it is characterized as a descriptive and explicative research, with a qualitative approach, based on the bibliographical and documentary research, which subsidizes the type of case study proposed, supported by interviews with organizational stakeholders selected for their involvement in the study strategic processes of the institutions. From the triangulation of the research subsidies, relevant impacts of the political factor and of the institutional context itself were identified in the effectiveness of strategic management in the military police investigated and in the perspective of the interviewees, with disparities in the process, in the registry and in its consolidation between the PMMG and BMRS. It is concluded that the practice of the former finds greater theoretical support as effective strategic management and that of the latter did not meet the requirements for such. Thus, the practices developed by the PMMG are adequate and possible for adoption in the BMRS or other PM, even with the limitations and differences of political and institutional context. It can be seen that the basic process of building a strategic planning was prioritized by the PMMG, and its adequate record of continuous improvement during the analyzed period allowed its understanding as a strategic police management by results, although there are difficulties for implementation and effectiveness in its entirety. At BMRS, the absence of strategic planning remained proven during the period and contributed to the fact that its management was not characterized as strategic. Finally, based on the understanding that strategies for continuous learning and benchmarking are relevant to streamline management processes, using the experiences and good practices identified in the research, at the end is presented a decalogue with suggestions for implementation of strategic management in the Brigada Militar.